Haploidentical Stem Cell Transplantation: A Gateway to Infrequent Availability of HLA-Matched Related Donors - Hafiz Muhammad Aslam; Shumaila Muhammad Iqbal; Hira Shaikh; Faizan A. Faizee; Ambreen A. Merchant; Marwan Shaheen; Shahrukh K. Hashmi (Case Reports in Medicine)
Haploidentical stem cell transplantation provides a plausible alternative for the patients when a fully matched donor is unavailable. Historically, the decision of considering haploidentical transplant has remained elusive; however, with the recent advances, the consideration of haploidentical grafts as a treatment option has become more apparent for both allografting for diseases and engraftment failure. We are reporting here an anecdotal case of a successful haploidentical engraftment in a patient with the prior graft failure of an HLA-matched related donor. Since the patient was severely alloimmunized, desensitization protocol was utilized before the haploidentical transplant, and the patient after 8 months of her second allogeneic transplantation is doing great with successful engraftment, no relapse, and no graft-versus-host disease (GVHD). Numerous reports pertinent to haploidentical graft have shown favorable outcomes in the graft placement, a decline in the rate of GVHD, and an improvement in the morbidity and mortality in affected individuals. Based on the current reports, haploidentical transplantation might be more feasible and has meaningful implications in the situations where matched donors are infrequent.